Extended reality for mapping perforator-based flaps in breast reconstruction: a systematic review and meta-analysis - Hester Lacey; Anas Khan; Baljit Dheansa (JPRAS Open)
Introduction: Extended reality technologies including augmented reality (AR) and virtual reality (VR) can be used in surgical settings for surgical planning, perioperative visualisation of patient anatomy and simulation of operative steps. This study aimed to ascertain the role of extended reality in perforator-based breast reconstruction. Methods: A systematic search of the literature was performed. Screening was conducted independently by two reviewers, with conflicts resolved through consensus. Results: In total, 4957 articles were identified of which 10 were included, comprising 229 flaps. Overall, localisation of perforator emergence with AR and VR were 4 mm (95% confidence interval [CI] 3.2-4.9) and 14 mm (95% CI 5.5-22.5), respectively, from the correct intraoperatively identified location. Two studies reported a significant reduction in harvesting time (88 min for VR and 19 min for AR). The pooled mean image processing time from four studies was 39±47 min. Preoperative VR was associated with shorter operative times than conventional Doppler ultrasound (478±56.94 vs 606.29 ± 81.94 min, P<0.05). Use of a simulated environment for mapping perforators appeared to reduce complications (wound breakdown, flap revision, flap loss, infection); however, this failed to reach statistical significance (odds ratio 0.6; 95% CI 0.3-1.3; P=0.20). Conclusions: This study suggests that AR and VR offer limited benefit in improving accuracy of perforator identification; however, they may reduce flap harvesting and total operative time. Key limitations include heterogeneity and quality of the included studies. With larger sample sizes and higher quality evidence, definitive benefits and longitudinal outcomes relating to use of extended reality in perforator-based breast reconstruction may be established.